Metacognitive Reading Strategies Used by Students in TOEFL Preparation Program at IAIN Palopo - Siti Raodha Salwi; Murni Mahmud; Kisman Salija (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research aims to reveal the types of metacognitive reading strategies used by students who have taken TOEFL preparation program at IAIN Palopo and to determine their perception towards use of it on their reading activities in the class. In investigating the research’s topic, the researcher applied mixed method with sequential explanatory design. It dealing with total of twelve students from English education study program in third and sixth semester as subject. The data were gathered trough semi-structure interview and Metacognitive Awareness of Reading Strategies Inventory (MARSI) questionnaire by Mokhtari and Reichard (2002) theory which was modified according to the research objective. The results showed that there were three types of metacognitive reading strategies with varying frequencies that students used namely: Global Reading Strategies (GLOB) with 36% as the highest usage, followed by Problem-solving Reading Strategies (PROB) and Support Reading Strategies (SUP), which equal with 32% usage. The researcher also found, most of the students have positive perception towards use of metacognitive reading strategies, even there were still a few students had negative perception. Furthermore, familiarity with concept, reading habit and learning environment be factors that influenced whether students viewed the metacognitive reading strategies positively or negatively.